Pengaruh Struktur Modal, Profitabilitas, dan Dewan Komisaris Independen Terhadap Nilai Perusahaan : Studi Empiris Pada Pada Perusahaan Sektor Consumer Non-Cyclicals Sub Sektor & Beverage Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023 - Dhelia Nurshafitri; Martini Martini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted with the aim of analyzing capital structure, profitability and independent board of commissioners. This research was conducted on Consumer Non-Cyclicals Sector Companies in the Food & Beverage Sub Sector listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling method in this research used a purposive sampling method with a sample of 43 non-cyclical consumer sector companies in the food & beverage sub-sector that met the sample criteria. This research uses multiple linear regression analysis techniques and uses the SPSS version 22.0 test tool. The results of this research show that the capital structure variables and independent board of commissioners have no effect on company value, while profitability has a positive and significant effect on company value